Associative Governance in Scandinavia: Organizing Societies by “Combining Together” - Anker Brink Lund; Haldor Byrkjeflot; Søren Christensen (Routledge, 2024)
This edited volume explores a variety of aspects of associative governance, providing detailed case studies of associations and associational governance in Scandinavia. Theoretically developing a concept and approach of associative governance, the book sheds light on a dynamic way of perceiving associative aspects of community and commercial life that has been hitherto underexplored and undertheorized. It shows how governance by associations may be conducted not only bottom‑up by self‑organized and voluntary participation, but also top‑down by authoritative incorporation through government, and – not least – in multifarious interstices in between. New section by exploring a vibrant panoply of dimensions of associative governance, empirically grounded in historical analyses of a wide range of organizational repertoires, the book may provide novel insights into the significant role of associative governance in Scandinavia over the past two centuries. Finally, it provides research‑based knowledge about how to maintain “good political and economic institutions” in the future and a more holistic and dynamic approach to the literature on The Nordic model. The book will be of key interest to scholars and students of Nordic and Scandinavian studies, history, sociology, political science, marketing, social policy, organization theory, and public management. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution‑Non Commercial‑No Derivatives (CC‑BY‑NC‑ND) 4.0 license.
Keywords: 650; Nordic societies; Scandinavia; governance; Scandinavian societies; Nordic governance; associative governance